Disasters and Tightness of Social Norms: The Case of Female Genital Cutting - Marianna Battaglia; John Egyir; Jorge Garcia-Hombrados (Institute of Labor Economics (IZA), 2025)
We examine the empirical relationship between exposure to disasters and tightness of social norms, focusing on the practice of female genital cutting (FGC) in Sub-Saharan Africa. Social norms tightness refers to the extent to which cultural groups enforce adherence to norms and punish deviations. It is a key factor in shaping how societies function and individuals behave, influencing everything from social order and conflict to collective effort and institutional dynamics, and often emerges and evolves as an adaptive response to adverse events. Drawing on occurrences of epidemics and natural disasters, we find that individuals surveyed in the aftermath of a disaster in their region adhere 4 to 6 percent of a standard deviation more closely to the opinions about FGC in their groups compared to those interviewed just before the disaster occurred. This effect is particularly pronounced among women and rural populations. By examining variations in early life exposure to disasters across birth cohorts within countries, we find that this effect persists over time and is strongest when the disaster occurs during the transition from childhood to early adolescence.
Keywords: D1; D7; I15; O1; O55; Z1; 330; social norms; cooperation; epidemics; natural disasters; Sub-Saharan Africa